EFFECT OF PLANT GROWTH REGULATORS AND MICRONUTRIENTS ON GROWTH AND YIELD OF VARIETIES OF GREENGRAM (Vigna radiata L.) - APNAGARI SRIDHAR; VIKRAM SINGH; DHANANJAY TIWARI; V.UDAY KIRAN (The Bioscan, 2021)
An experiment was carried out during Kharif season 2019 at Crop Research Farm, NAI, SHUATS to study about the Effect of plant growth regulators and micronutrients on growth and yield of varieties of Green gram (Vigna radiata L.). The experiment consisted of 10 treatments which includes Two varieties of green gram i.e. SAMRAT and VERSHA-563 was used with different concentrations of Plant Growth regulators Salicylic acid 100, 200 ppm, and micronutrients zinc 100 ppm and boron 100 ppm of each concentration and one respective control was used. The result showed that growth parameters viz,plant height (40.63cm) at 60DAS, Dry weight (7.93 g/ plant) at 60DAS were recorded superior with application of salicylic acid 200 ppm in variety samrat. Nodules/ plant (22.67) at 60 DAS were recorded superior with application of ZnSO 4 100 ppm in variety samrat. The yield parameters viz, pods per plant (38.33), Grain yield (1115.15 kg/ ha), Stover yield (2465.28 kg/ha) were recorded superior with the application of salicylic acid 200 ppm in variety samrat.Growth and yield characteristics were enhanced by application of salicylic acid 200 ppm in Samrat variety. So, based on results Samrat variety with salicylic acid 200 ppm consider to be the suitable combination to increasing greengram production.